Value of bevacizumab in treatment of colorectal cancer: A meta-analysis - Qu, Chun-Ying (World J Gastroenterol, 2015)
AIM: To assess the efficacy and safety of bevacizumab in the treatment of colorectal cancer. METHODS: All randomized controlled trials of bevacizumab for the treatment of colorectal cancer from January 2003 to June 2013 were collected by searching the Cochrane Library, PubMed, Chinese National Knowledge Infrastructure and Wanfang databases. The primary endpoint was overall survival (OS), and the secondary endpoints were progression-free survival, overall response rate and adverse events. Two reviewers extracted data independently. Statistical analyses were performed with Stata 12.0. The degree of bias was assessed using funnel plots for the effect size of OS at the primary endpoint. RESULTS: Following the inclusion criteria and exclusion criteria, ten studies comprising 6977 cases were finally included, of which nine were considered to be of high quality (4-7 points) and one of low quality (1-3 points). Our meta-analysis revealed the efficacy of bevacizumab in patients with colorectal cancer in terms of OS (HR = 0.848, 95%CI: 0.747-0.963), progression-free survival (HR = 0.617, 95%CI: 0.530-0.719), and overall response rate (OR = 1.627, 95%CI: 1.199-2.207). Regarding safety, higher rates of grade ≥ 3 hypertension, proteinuria, bleeding, thrombosis, and gastrointestinal perforation were observed in the bevacizumab treatment group (P < 0.05); however, the incidence of serious toxicity was very low. There was no publication bias in the 10 reports included in this meta-analysis. CONCLUSION: The clinical application of bevacizumab in colorectal cancer is effective with good safety.